2004
DOI: 10.1021/jf035491w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Betalains from Petioles of Differently Colored Swiss Chard (Beta vulgaris L. ssp. cicla [L.] Alef. Cv. Bright Lights) by High-Performance Liquid Chromatography−Electrospray Ionization Mass Spectrometry

Abstract: The betalain pattern of differently colored Swiss chard (Beta vulgaris L. ssp. cicla [L.] Alef. cv. Bright Lights) was investigated for the first time. Nineteen betaxanthins and nine betacyanins were identified by RP-HPLC and positive ion electrospray mass spectrometry, co-injection experiments with semisynthetic reference compounds, and standards derived from authentic plant material, respectively. Histamine-betaxanthin and alanine-betaxanthin were found to be novel betaxanthins, which to the best of our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
1
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 34 publications
8
126
1
10
Order By: Relevance
“…Purity was confirmed by HPLC analysis with PDA detection. Masses were as expected for the corresponding protonated molecular ions [M+H] + of the pigments: m/z 331 (tyraminebetaxanthin) and m/z 347 (dopamine-betaxanthin), as previously reported (Kugler et al 2004). …”
Section: Chemical Synthesis and Purification Of Betaxanthins Derived supporting
confidence: 82%
See 2 more Smart Citations
“…Purity was confirmed by HPLC analysis with PDA detection. Masses were as expected for the corresponding protonated molecular ions [M+H] + of the pigments: m/z 331 (tyraminebetaxanthin) and m/z 347 (dopamine-betaxanthin), as previously reported (Kugler et al 2004). …”
Section: Chemical Synthesis and Purification Of Betaxanthins Derived supporting
confidence: 82%
“…inflorescences ). Tyramine-derived betaxanthin (miraxanthin III) is a betaxanthin also described in Mirabilis jalapa flowers, (Piattelli et al 1965) and in colored Swiss chard (Kugler et al 2004). Fig.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It had been reported that dopaxanthin was the only pigment in Glottiphylum longum flowers (0.3 mg g 21 ; Impellizzeri et al, 1973). This single pigment composition is not usual in the distribution of betaxanthins, which are frequently reported to appear in mixtures (Piattelli et al, 1965;Kugler et al, 2004). The data published for Glottiphylum were reviewed by using the analytical tools available today, studying in this case the species Glottiphylum oligocarpum and Glottiphylum pigmaeum.…”
Section: Extraction and Purification Of Dopaxanthin From Yellow Flowementioning
confidence: 99%
“…Miraxanthin V (2) was first identified in flowers of Mirabilis species, and its structure was elucidated by 1 H-NMR analysis on a 60-MHz spectrometer [9]. According to more-recent reports, this betaxanthin has also been detected in common cockscomb, feathered amaranth, yellow beet, and Swiss chard [16] [23] [24].…”
Section: A C H T U N G T R E N N U N G Co 2 a C H T U N G T R E N N Umentioning
confidence: 99%